Airports as liminal space. (May 2018) - Huang, Wei-Jue; Xiao, Honggen; Wang, Sha
Highlights: Airports are liminal spaces. This study presents a phenomenology of passenger experience in international airports. Passenger experience varies in accordance to his/her familiarity with an airport. Consumption rituals are characteristic of frequent passengers in familiar airports. Experienced passengers tend to see airports as a personal space and free time. Abstract: More than a mere transport facility, airports serve as a multifunctional space for social interactions and individual/personal experiences that break geographical boundaries and secular distinctions. This study explores the liminal nature of airports as a micro-destination and presents a phenomenology of passenger experience in accordance to their familiarity with the space. The nature of airports as a liminal space ranges from touristic experience of first-timers to consumer rituals of frequent visitors. Liminality is derived from passenger watching and assistance offering to strangers, whereby a sense of communitas is felt in a secure and often facilitating environment. For frequent flyers, airports are utilized as mobile office space or "free time", indicative of contemporary travelers' need for slow life and quality alone-time.